ANALISIS KARAKTERISTIK KOMITE RISIKO TERHADAP KINERJA KEUANGAN - Mokoginta, Dirgantara Dahana (Politeknik Negeri Ambon, 2021)
Research on risk committees of companies outside the financial sector is still very rarely studied, especially in Indonesia. This study analyze characteristics of risk committee and financial performance of companies outside the financial sector of the Indonesia Stock Exchange. The year of observation is from 2013 to 2020. Based on purposive sampling, 219 data were found. The data processed using SPSS. The risk committee characteristics examined are the number of members, the percentage of meeting attendance, gender diversity, members with financial expertise, and independence. The results showed that none of these characteristics effect on financial performance. This research conclude that risk committee in companies outside the financial sector still appears as a mere formality. This conclusion supported by the statistical frequency test which shows that there is a high percentage of board interlock in the risk committee members, which is 65 percent of members having board interlock, and the mode value is 100 percent of risk committees having board interlock members.